2011
DOI: 10.1055/s-0031-1285928
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Treadmill and Cycle Exercise

Abstract: This study aimed to identify differences in the acute cardio-respiratory, metabolic and perceptual responses between exercise performed on the treadmill and on the cycle ergometer at several intensities. The sample comprised of 20 voluntary male participants (age=22.5 ± 1.8 years; height=177.7 ± 7.0 cm; body mass=72.6 ± 7.9 kg; fat mass=7.87 ± 1.3%) that performed 5 submaximal 8 min exercise bouts, interspersed with a 10 min period of passive recovery. Exercise intensity used on the treadmill was 10, 12, 14, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 26 publications
6
36
0
2
Order By: Relevance
“…_ VO 2 max values were lower using cycle ergometry compared with a treadmill machine for exercise testing; this systematic difference has previously been reported when intra-subject comparisons of both methods were made in the same study. 20,21 Therefore our pooled results should be interpreted cautiously. Our sensitivity analysis also showed that treadmill testing is more likely to identify differences in _ VO 2 max compared to cycle ergometry.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…_ VO 2 max values were lower using cycle ergometry compared with a treadmill machine for exercise testing; this systematic difference has previously been reported when intra-subject comparisons of both methods were made in the same study. 20,21 Therefore our pooled results should be interpreted cautiously. Our sensitivity analysis also showed that treadmill testing is more likely to identify differences in _ VO 2 max compared to cycle ergometry.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies comparing the methods used to predict _ VO 2 max have shown that a treadmill running test gives higher results by 5-15% than the cycle ergometer test and the sensitivity analysis confirmed this finding. 20,35,36 Despite the limitations, the meta-analysis for _ VO 2 max shows that preterm-born subjects with or without BPD have lower (<13%) exercise capacity than term-born control subjects. The differences in _ VO 2 max are small (À2.20 ml/kg/min to À3.05 ml/kg/min; SMD À0.33 to À0.44) and it would appear that despite the increased risk of cardio-respiratory problems of preterm-born subjects with or without BPD, they are able to achieve near normal exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has directly investigated the extent to which the exercise modality affects the relationship between GET and HRVT. Considering that HRV varies according to exercise mode (21) and that the physiological strain (measured by peak heart rate and V˙O2 peak) seems to be significantly greater during treadmill exercise than during cycle ergometry (22,23), it is thus reasonable that the level of agreement between the GET and HRVT may also be affected by exercise modality. Another unanswered question is whether the intensity of aerobic exercise can be accurately prescribed using the heart rate response associated with GET and HRVT, by assuming a 1:1 relationship between the %HRR and %V˙O2 R.…”
Section: Introductionmentioning
confidence: 99%
“…De maneira conjunta esses estudos controversos apresentam determinadas similaridades, como por exemplo, a especificidade do grupo amostral pesquisado, que é composto por mulheres (DAY et al 2007) e atletas com alto níveis de treinamento (RANKINEN et al 2000;GOMEZ-GALEGO et al 2009). Outra similaridade é o ergômetro utilizado, ciclo ergômetro de perna, o que pode limitar os resultados, visto que os resultados em um único tipo de ergômetro não podem ser extrapolados para outros tipos de exercícios, além disso, esse ergômetro apresenta características específicas que podem influenciar na comparação (BASSET e HOWLEY 1997;ABRANTES et al 2012). De maneira conjunta, esses estudos conseguem criar uma teoria concisa para refutar a teoria inicial de associação do polimorfismo da ECA com modalidades esportivas, mais especificamente, o genótipo II com modalidades predominantemente aeróbias.…”
Section: Polimorfismo Da Eca E Aptidão Aeróbiaunclassified
“…Isso é especialmente importante, haja vista que durante o exercício em cicloergômetro há uma tendência de que indivíduos com maiores valores de força muscular, muito comum em indivíduos DD, podem apresentar melhores resultados. Acredita-se que o desempenho em testes realizados nesse ergômetro é altamente influenciado por fatores musculares, incluindo a força muscular e a resistência à fadiga periférica(BJKER et al 2002;ABRANTES et al 2012).Dessa forma, o presente estudo teve como uns de seus objetivos analisar a influencia dos genótipos da ECA sobre os valores das variáveis submáximas associadas com a aptidão aeróbia, a saber, LV, PCR e EC em duas intensidades submáximas, durante a corrida. Para tanto, a amostra foi inicialmente dividida de acordo os genótipos, em um segundo momento foi comparado os valores de cada variável submáxima por grupo.…”
unclassified